(3eaGJjM GdYdGbGJ GdGbJUGOjI GdOhdjIs - (3eMeO(B, (3QGJhds ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2018)
(3GdcJGH GdPj Hjf jOjc YHGQI Yf eLehYI ef GdeMGVQGJ GdefbMI aj eNJda ehGVjY GdGbJUGO GdOhdj h GdYdGbGJ GdGbJUGOjI GdOhdjI, bOeJgG Ydi aJQGJ dWdHI GdYdhe GdGbJUGOjI h GdJLGQjI, efP SfI (B2000(3, h bO RGefJgG HJMOjKGJ eSJeQI MSH GdCMOGK h GdJWhQGJ GdGbJUGOjI h GdeGdjI GdOhdjI, h bO GYJeOJ aj JbOjegG Ydi GdHSGWI aj GdSQO h GdWQM, eY EYWGA CeKdI JhVjMjI cdeG JWdH GdCeQ Pdc, dJSgjd age GdehGVjY hGSJjYGHgG, dJchf ebOeI h eaGJjM dage hJMdjd cd eG jOhQ ef CMOGK h hbGFY Ydi eSJhi GdYdGbGJ GdGbJUGOjI GdOhdjI, h bO JLfHJ GdcKjQ ef GdJaGUjd h GdGSbGWGJ Ydi GdHdOGf eQGYjG aj Pdc GdMLe GdCeKd ddcJGH Ohf EaQGW aj GdCSGSjGJ GdJj jLH Ydi GdWGdH EOQGcgG EdRGeG, hbO GJHYJ aj Pdc efgLjI efWbjI h dZI HSjWI SgdI Gdage HYjOI Yf GdJYbjOGJ GdJj JLYd GdbGQjA jMS HGdedd h Kbd GdCSdhH(B. (3h GdcJGH ehLg djS abW dWdHI Ydhe GdGbJUGO, GfeG dcGaI WdHI cdjGJ heOGQS h eYGgO Ydhe GdGbJUGO h GdJSjjQ h GdJLGQI, h GdYdhe GdSjGSjI h GdGYdGe aj eSJhjGJ GdJOQL h eG HYO GdJOQL, h cd OGQS h egJe HGdGbJUGO GdOhdj hGdYdGbGJ GdGbJUGOjI GdOhdjI(B. s
(3eQGLY U(B.365s
Keywords: (3GdGbJUGO GdOhdjs